Changing world, changing trusts and health providers' sufferings - Shakunatala Chhabra (Wolters Kluwer Medknow Publications, 2019)
Workplace violence (WPV) is a serious problem anywhere, but is one of the most complex issues in health settings. Many factors contribute to WPV is health setting, health workers functioning in stressful environment, 24-h access to many, presence of drugs, and human sufferings with limitations in care. Violence may take a variety of forms, verbal aggression to physical assault, use of deadly weapons against physicians, others, and even patients. It is, therefore, associated with a variety of risks to workers safety, as well as organizational liability. The objective was to know happenings and challenges in the prevention of violence against health providers. This simple review of available studies and opinions was done by using Uptodate, ERMED CONSORTIUM, Cochrane Library, Delnet, and MedIND, and self-experiences were added. Physical violence (PV) against doctors and other health personnel is increasingly being reported. It is believed that more than 75% of doctors face violence during their practice. Almost half of the violent incidents occur in critical care units. WPV has been categorized into physical and mental, but all types of violence are destructive, in one or other way. There is evidence that female health workers are exposed to PV more often than others. It is essential to identify risk factors in order to prevent and manage WPV against health providers. Reasons for violent outbursts include inadequate workforce, infrastructure to treat patient load, and long waiting times. Many health personnel never report exposure of violence to anyone because of various reasons including perception that reporting was useless. Though it is difficult to completely eliminate violence in health-care settings, and although there is no "one-size-fits-all" approach for prevention, there are many ways to reduce the potential for violent occurrences and to minimize the impact if violence does occur.